The Immune Microenvironment in Human Papilloma Virus-Induced Cervical Lesions—Evidence for Estrogen as an Immunomodulator - R. S., Jayshree (Frontiers in Cellular and Infection Microbiology, 2021)
Globally, human papilloma virus (HPV) infection is a common sexually transmitted disease. However, most of the HPV infections eventually resolve aided by the body’s efficient cell-mediated immune responses. In the vast majority of the small group of patients who develop overt disease too, it is the immune response that culminates in regression of lesions. It is therefore a rarity that persistent infection by high-risk genotypes of HPV compounded by other risk factors progresses through precancer (various grades of cervical intraepithelial neoplasia—CIN) to cervical cancer (CxCa). Hence, although CxCa is a rare culmination of HPV infection, the latter is nevertheless causally linked to >90% of cancer. The three ‘Es’ of cancer immunoediting viz. elimination, equilibrium, and escape come into vogue during the gradual evolution of CIN 1 to CxCa. Both cell-intrinsic and extrinsic mechanisms operate to eliminate virally infected cells: cell-extrinsic players are anti-tumor/antiviral effectors like Th1 subset of CD4+ T cells, CD8+ cytotoxic T cells, Natural Killer cells, etc. and pro-tumorigenic/immunosuppressive cells like regulatory T cells (Tregs), Myeloid-Derived Suppressor Cells (MDSCs), type 2 macrophages, etc. And accordingly, when immunosuppressive cells overpower the effectors e.g., in high-grade lesions like CIN 2 or 3, the scale is tilted towards immune escape and the disease progresses to cancer. Estradiol has long been considered as a co-factor in cervical carcinogenesis. In addition to the gonads, the Peyer’s patches in the gut synthesize estradiol. Over and above local production of the hormone in the tissues, estradiol metabolism by the gut microbiome: estrobolome versus tryptophan non-metabolizing microbiome, regulates free estradiol levels in the intestine and extraintestinal mucosal sites. Elevated tissue levels of the hormone serve more than one purpose: besides a direct growth-promoting action on cervical epithelial cells, estradiol acting genomically via Estrogen Receptor-α also boosts the function of the stromal and infiltrating immunosuppressive cells viz. Tregs, MDSCs, and carcinoma-associated fibroblasts. Hence as a corollary, therapeutic repurposing of Selective Estrogen Receptor Disruptors or aromatase inhibitors could be useful for modulating immune function in cervical precancer/cancer. The immunomodulatory role of estradiol in HPV-mediated cervical lesions is reviewed.